Championing Dementia Education: Adapting an Effective Scottish Dementia Education Program for Canadian Acute Health Care Providers. Issue 1 (10th March 2023) - Peacock, Shelley; Bayly, Melanie; Fletcher-Hildebrand, Shaneice; Gibson, Kirstian; MacRae, Rhoda; Jack-Waugh, Anna; Haase, Kristen; Bally, Jill; Duggleby, Wendy; Hall, Steven; Holtslander, Lorraine; McAiney, Carrie; et al.
Abstract: With increasing numbers of persons living with dementia and their higher rates of hospitalizations, it is necessary to ensure they receive appropriate and effective acute care; yet, acute care environments are often harmful for persons with dementia. There is a lack of dementia education for acute health care providers in Canada. Scotland presently delivers a dementia education program for health care providers, known as the Scottish National Dementia Champions Programme. The objective of this Policy and Practice Note is to present the collaborative work of Scottish experts and Canadian stakeholders to adapt the Dementia Champions Programme for use in Canada. This work to date includes: (a) an environmental scan of Canadian dementia education for acute health care providers; (b) key informant interviews; and, (c) findings from a two-day planning meeting. The results of this collaborative work can and are being used to inform the next steps to develop and pilot a Canadian dementia education program.